Waste cathode-ray-tube glass powder modified asphalt materials: Preparation and characterization. (10th September 2021) - Jin, Dongzhao; Wang, Jiaqing; You, Lingyun; Ge, Dongdong; Liu, Chaochao; Liu, Hongfu; You, Zhanping
Abstract: Cathode-ray-tube (CRT) is the ingredient of glass used in obsolescent televisions or computer monitors. CRT glass contains a considerable amount of heavy metals, and the landfilling of CRT glass is significantly harmful to the environment. In an effort to recycle waste CRT glass instead of landfilling it, recycled CRT glass powders were introduced to asphalt binders as a modifier in this preliminary investigation. The recycled CRT glass was processed to a particle size smaller than 0.075 mm and mixed with asphalt binder (PG 58–28) to produce asphalt mastics with four different concentrations (0, 5, 10, and 15 wt%). The rheological performance was characterized with the rotational viscosity (RV), dynamic shear rheometer (DSR), and multiple stress creep recovery (MSCR) tests. The fatigue performance was evaluated by linear amplitude sweep (LAS) test. Meanwhile, the low-temperature properties were measured by the asphalt binder cracking device (ABCD). The hazard materials leaching test was applied to evaluate the leaching potential of lead content into the external environment due to the high lead content in the modified asphalt. The test results revealed that the increase of CRT glass powder content improved the energy of activation compared with that of virgin binder, as well as the resistance of permanent deformation. Furthermore, the incorporation of CRT glass powder may slightly increase the fatigue life of asphalt because of the improved physicochemical interaction between glass and bitumen. The low-temperature cracking temperature first decreased with the increase of CRT glass powder content and then increased as the CRT content increased further. The leaching test demonstrated that the CRT glass powders incorporated into asphalt binders represented a lower lead leaching content than that of the original CRT glass powder, where the lead leaching amount of CRT glass modified asphalt binder is obviously lower than the specified level of 5 mg/L. Therefore, it is possibly acceptable to recycle CRT glass powders in asphalt binders as an additive as an environmental-friendly recycling method, in which the optimal addition content of CRT glass powders could be up to 10% (wt.).